Applying safety management systems in general aviation - Schreiber, Clarence J. (Kansas State University, 2024)
Safety Management Systems within aviation are not required for Part 91 general aviation flight operations. However, the failure to establish industry best practices that voluntarily incorporate safety management within their respective flight operations is referenced in the National Transportation Safety Board post-accident findings and recommendations. Aviation Safety Management Systems are pointedly referenced as scalable to individual flight operations; however, the Federal Aviation Administration does not offer an example template at any levelfor aviation organizations or service providers to follow. This capstone project aims to demonstrate the necessity for flight organizations to voluntarily implement safety management and how a flight operation that does not require a safety management program can develop a program that meets established industry best practices scaled to their unique operations.
Keywords: Aviation; Safety management; Highway patrol